2018
DOI: 10.11118/ejobsat.v4i2.132
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Dividend Policy in Bangladesh: Survey Evidence from Listed Manufacturing Companies in Dhaka Stock Exchange

Abstract: A firm considers various factors when approaching a dividend policy decision. To analyze the determinants of dividend policy in the context of Bangladesh, questionnaire survey has been done from financial decision makers of sample companies. The nonparametric test and factor analysis is used for interpreting results. The research finding exhibits that in the first stage, the economic related factor, legal constraint factor, capital market related factor, residual policy factor, capital source factor and client… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…According to Anil and Kapoor (2008), profitability is the most important sign of DPR. Adaoglu (2000) researched emerging markets and argued that the main determinants of cash dividends are current-year earnings and emerging market firms follow unstable dividend payout policies which is also supported by Mahira (2012) and Islam and Adnan (2019). Le, Nguyen, and Tran (2019); Al-Kuwari (2009); Naceur, Goaied, and Belanes (2006); Patra, Poshakwale, and Ow-Yong (2012); Amidu and Abor (2006) and Jabbouri (2016) found a significant affirmative connection between profitability and DPP.…”
Section: Literature Reviewmentioning
confidence: 84%
See 2 more Smart Citations
“…According to Anil and Kapoor (2008), profitability is the most important sign of DPR. Adaoglu (2000) researched emerging markets and argued that the main determinants of cash dividends are current-year earnings and emerging market firms follow unstable dividend payout policies which is also supported by Mahira (2012) and Islam and Adnan (2019). Le, Nguyen, and Tran (2019); Al-Kuwari (2009); Naceur, Goaied, and Belanes (2006); Patra, Poshakwale, and Ow-Yong (2012); Amidu and Abor (2006) and Jabbouri (2016) found a significant affirmative connection between profitability and DPP.…”
Section: Literature Reviewmentioning
confidence: 84%
“…In Bangladesh, the majority of research focuses on local businesses. Research on manufacturing businesses listed on the DSE was carried out by Islam and Adnan (2019). Recently, there has not been a DPP study on MNCs in Bangladesh that focuses on DSE.…”
Section: Financial Risk and Management Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Islam and Adnan (2018) observed that liquidity and present earnings are the most important determinants for the listed companies of Bangladesh in shaping their dividend policy. 27 The empirical results of the study of Mollah (2009) recommended that dividend pronouncements are mostly directed by lagged dividends and current profitability of companies listed on Dhaka Stock Exchange. Cash flow is recognized as a superior measure of the company's capability to pay dividends.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%